Phylogenetic relationships and a new classification of the family Cyclopteridae (Perciformes: Cottoidei) - Oku, Kanami; Imamura, Hisashi; Yabe, Mamoru (Zootaxa, 2017)
Phylogenetic relationships of the family Cyclopteridae were reconstructed based on osteological and external characters.  The monophyly of the family was strongly supported by 47 commonly recognized synapomorphies, including six autapomorphies (plus one additional autapomorphy, presence of a dorsal process on the pelvis, recognized after the phylogenetic analysis) among the suborder Cottoidei.  As a result of the cladistic analysis, a single most parsimonious phylogeny was obtained, based on characters in 32 transformation series.  A new classification of Cyclopteridae based on reconstructed relationships, including three subfamilies [Liparopsinae, Cyclopterinae and Eumicrotreminae (newly established)] and four genera (Aptocyclus, Cyclopsis, Cyclopterus and Eumicrotremus), is proposed.